7 - Les difficultés de l’intégration inter-industrielle en Algérie et la dépendance technologique - Abdelkader DJEFLAT (Africa Development, 1985)
One of the models used in African economies to break away from technological dependence is the one known as state-controled industria lization. The opening up to the outer world which is its major feature is one of the conditions for its implementation as well as a major source of obstruction and, in the long-run, of a questioning of the very efficiency of the model, as a strategy of parting from classical forms of periphery capitalism. The Algerian model of economic development focuses on the internal dynamics of inter-industrial integration — Its industrialization pattern presented as a model of controled opening with promises of gra dual autonomy reveals inadequacies and limitations both at the theore tical and practical levels. In this model, the Algerian Planner resorted to various forms of technology transfer. The integral form which is most often used in the petroleum industry backed and even added to the open ing towards the world market. The use of fragmented forms in the case of the iron-steel industry corresponds to an attempt to drastically limit this opening. However, this attempt largely depends on local technological capacities. The opening through technology leads to a number of difficulties, at the level of inter-sectoral integration. Such an opening tends to reproduce the conditions of the world market at the local level, in the export sector as well as the othei sectors which are related to it. Another consequence of the use of more and more sophisticated technologies is a wider opening accompanied by a gradual disqualification of local labour, hence an increased import of qualified labour. This opening to the world market also exposes local economic equilibria to the effects of the crisis now taking place at the Centre. A more elaborate analysis of the differentiated effects of the crisis at the level of all the sectors would help in assessing the real capacity of the model of state-controled industrialization to break away from the Centre.